Corn yield with reduction of insecticidal sprayings against fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) - Pogetto, M. H. F. A. dal [UNESP]; Prado, E. P. [UNESP]; Gimenes, M. J. [UNESP]; Chnstovam, R. S. [UNESP]; Rezende, D. T. [UNESP]; Aguiar-Júnior, H. O. [UNESP]; Costa, S. I. A. [UNESP]; Raetano, Carlos Gilberto [UNESP] (Science Alert, 2012)
The ideal time is more important than amount of insecticidal spraying to adequate the control of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) in corn. This study aimed to evaluate lufenuron sequential sprayings effect and its rotation with other active ingredients on the population, damage caused by S. frugiperda and the impact on corn yield. The experiment was carried out in the field with six treatments: (1) one lufenuron spraying, (2) two lufenuron sprayings, (3) three lufenuron sprayings (4) four lufenuron sprayings, (5) sprayings with spinosad, lufenuron, thiamethoxam+lambdacyhalothrin and deltamethrin (in sequence, at ten days intervals) (6) control treatment. Sprayings started twenty days after the seedling had emerged and then every ten days for a maximum of four sprays. Both caterpillar population (20.9-21.7 larvae/plot) and index of damage (1.2-1.7) observed in corn plants were significantly lower in treated plots compared to control (untreated) (31.7 larvae/plot and index of damage 2.7), regardless of spraying amount. The results showed that multiple insecticide applications to control S. frugiperda do not guarantee higher yields in corn, ranging from 6375.2 to 7650.1 kg ha -1. Only one spraying of lufenuron was enough to prevent significant reduction in corn yield (6749.9 kg ha -1). © 2012 Asian Network for Scientific Information.
Keywords: Damage threshold; Lufenuron; Pest control; Spraying season; Zea mays; Lepidoptera; Noctuidae; Spodoptera frugiperda